2018–2019 Florida Citrus Production Guide: Pesticide Application Technology: ABE-356/CG024, rev. 5/2018 - Salyani, Masoud (EDIS, 2019)
This 8-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by Masoud Salyani and published by the Department of Agricultural and Biological Engineering, May 2018. ABE-356/CG024: 2022–2023 Florida Citrus Production Guide: Pesticide Application Technology (ufl.edu)